Strategic Monitoring and Its Impact on Organizational Sustainability: An Analytical Study in Baghdad Health Directorates (Karkh, Rusafa, and Medical City) - Rahal, Rawad; Adel Hamid, Suhair (Journal of Economics and Administrative Sciences, 2025)
This paper analyzes how Strategic Monitoring (SM) affects the Organizational Sustainability (OS) of some selected Baghdad Health Directorates in Iraq and attempts to establish how economic, social, and environmental sustainability can be achieved through SM, which includes strategic intelligence, strategic thinking, and strategic vigilance. A descriptive-analytical methodology has been used in which data was gathered using a structured questionnaire administered to 60 middle management officials of the directorates. The data were processed through suitable statistical tools using regression and correlation methods with the help of SPSS software. Results indicate that there exists a strong and significant positive relationship between SM and OS, with SM accounting for 65.6% variance in sustainability outputs. The two dimensions of SM having the greatest impact upon OS were found to be strategic intelligence and strategic thinking, followed by strategic vigilance. This will stress supporting and developing the SM capabilities in fighting environmental challenges, enhancing responsiveness, and ensuring sustain performances. From a practical standpoint, the study implies that the health sector's decision-makers can capitalize on embedding strategic monitoring practices to enhance decision-making and foster long-term sustainability. The study fills a much-needed gap in literature by providing an empirical connection between SM and OS in the public health setting. This promotes institutional mechanisms stressing continuous learning, environmental scanning, and proactive leadership.